(untitled) (Ukrainian Journal of Ophthalmology, 2026)
In this day and age of information technology and significantly accelerated scientific and technical progress in all fields of knowledge including ophthalmology, it is crucial for scientific results obtained to be published as quickly as possible. However, experience has shown that this is obviously not enough. It is required, for these results, to be available worldwide. Therefore, scientific papers in ophthalmology must be published in such a journal which is included in major world databases and which, in addition, has papers with an open access and with full texts, not only abstracts, properly translated into English.